Matrix metalloproteinase-7 disrupts dendritic spines in hippocampal neurons through NMDA receptor activation - Bilousova, Tina V. (2006)
Dendritic spines are protrusions from the dendritic shaft that host most excitatory synapses in the brain. Although they first emerge during neuronal maturation, dendritic spines remain plastic through adulthood, and recent advances in the molecular mechanisms governing spine morphology have shown them to be exquisitely sensitive to changes in the micro-environment. Among the many factors affecting spine morphology are components and regulators of the extracellular matrix (ECM). Modification of the ECM is critical to the repair of injuries throughout the body, including the CNS. Matrix metalloproteinase (MMP)-7/matrilysin is a key regulator of the ECM during pathogen infection, after nerve crush and in encephalitogenic disorders. We have investigated the effects of MMP-7 on dendritic spines in hippocampal neuron cultures and found that it induces the transformation of mature, short mushroom-shaped spines into long, thin filopodia reminiscent of immature spines. These changes were accompanied by a dramatic redistribution of F-actin from spine heads into thick, rope-like structures in the dendritic shaft. Strikingly, MMP-7 effects on dendritic spines were similar to those of NMDA treatment, and both could be blocked by channel-specific antagonists. These findings are the first direct evidence that MMPs can influence the morphology of mature dendritic spines, and hence synaptic stability.